Kesadaran Pelaku Usaha Kuliner di Ponorogo Tentang Jaminan Makanan Halal - Syafa Tasya Wahyuleananda; Iza Hanifuddin; Luhur Prasetiyo (Journal of Economics, Law, and Humanities, 2024)
This research is motivated by a lack of halal awareness starting from the level of understanding and knowledge of business actors. Restaurant business owners in Ponorogo must of course improve the safety, health and halal quality of their products. The problem of the low level of halal awareness among culinary business actors in Ponorogo requires the involvement of all stakeholders, including the government as part of elements of society, to provide good efforts to the Muslim community, in particular, such as carrying out intensive outreach and education and mentoring. This research uses field research (Field Research) with a qualitative approach. Data collection techniques use observation, interviews and documentation. Researchers conducted interviews with culinary business owners, staff, employees, parties involved and consumers. This research uses data analysis with an inductive method. The aim of this research is to analyze the knowledge, understanding, attitudes and actions of culinary business actors regarding halal food guarantees. Apart from that, to identify the factors that cause the low level of halal awareness among culinary business actors in Ponorogo. The results of this research are that culinary business actors' knowledge and understanding of halal products is still low. Knowledge and understanding regarding the acquisition of raw materials and production processes is limited to reaching the closest locations, without checking halal labels, content and expiry of the products purchased. However, based on observations, the products they use are certified halal. Meanwhile, facilities during production need to be improved, especially for animal slaughter. Furthermore, regarding knowledge about how to get a halal product certificate, business people are very unfamiliar with it and socialization and education are needed to change their mindset about products.